Development of Lentiviral Vectors for HIV-1 Gene Therapy with Vif-Resistant APOBEC3G - Delviks-Frankenberry, Krista A. (Mol Ther Nucleic Acids, 2019)
Strategies to control HIV-1 replication without antiviral therapy are needed to achieve a functional cure. To exploit the innate antiviral function of restriction factor cytidine deaminase APOBEC3G (A3G), we developed self-activating lentiviral vectors that efficiently deliver HIV-1 Vif-resistant mutant A3G-D128K to target cells. To circumvent APOBEC3 expression in virus-producing cells, which diminishes virus infectivity, a vector containing two overlapping fragments of A3G-D128K was designed that maintained the gene in an inactive form in the virus-producer cells. However, during transduction of target cells, retroviral recombination between the direct repeats reconstituted an active A3G-D128K in 89%–98% of transduced cells. Lentiviral vectors that expressed A3G-D128K transduced CD34(+) hematopoietic stem and progenitor cells with a high efficiency (>30%). A3G-D128K expression in T cell lines CEM, CEMSS, and PM1 potently inhibited spreading infection of several HIV-1 subtypes by C-to-U deamination leading to lethal G-to-A hypermutation and inhibition of reverse transcription. SIVmac239 and HIV-2 were not inhibited, since their Vifs degraded A3G-D128K. A3G-D128K expression in CEM cells potently suppressed HIV-1 replication for >3.5 months without detectable resistant virus, suggesting a high genetic barrier for the emergence of A3G-D128K resistance. Because of this, A3G-D128K expression in HIV-1 target cells is a potential anti-HIV gene therapy approach that could be combined with other therapies for the treatment and functional cure of HIV-1 infection.